(untitled) (Research, Society and Development, 2024)
This study aimed to analyze the in vivo anti-tumor effect of silver nanoparticles (AgNPs) against oral and skin cancer. The PRISMA guidelines were followed, and a registration in PROSPERO was performed. A search of databases was carried out in September 2023. The data were analyzed using the inverse variance method with a random effect model. All studies assessed anti-tumor efficacy against melanoma, and 21 days after treatment with AgNPs showed a reduction in tumor volume (SMD -6.58; PI [-9.82, -3.34]). Administration of AgNPs in injectable and topical form was effective in reducing tumors, erythema and preventing metastases without causing side effects. We concluded that AgNPs showed antitumor action against mice melanoma by reducing tumor volume and preventing cell proliferation and metastasis.